Multiscale Microstructure for Investigation of Cell–Cell Communication. Issue 12 (9th October 2020) - Schneider, Ann‐Kathrin; Scharnweber, Tim; Cammann, Destiny; Rapp, Bastian; Giselbrecht, Stefan; Niemeyer, Christof M.
Abstract: A multiscale polydimethylsiloxane (PDMS) chip is presented, which provides an array of mesoscale open wells for cell culturing and, as unique feature, an array of microscale 1 µm deep channels to fluidically connect neighboring wells. As demonstrated with SH‐SY5Y cells, the small dimensions of the channels prevent migration of the cell soma but allow physical contacts established by the outgrowth of protoplasmic protrusions between cells in adjacent wells. Another important feature is the chip's mountability on solid substrates, such as glass. This enables the use of substrates previously patterned with biomolecules, as demonstrated by DNA‐directed immobilization of proteins inside the reactor wells. Given the versatile addressability of cells, whether through surface‐bound or inkjet‐based administration of bioactive substances, it is believed that the reactor could be used for research in cell–cell communication networks, for example, in neurodegenerative diseases such as Alzheimer's disease. Abstract : A multiscale polydimethylsiloxane (PDMS) microstructure with wells and small connecting channels enables the culture of neural cells with the formation of cell–cell contacts between cell populations in adjacent wells. Since both dissolved and surface‐bound bioactive substances can be investigated, the chip could be used for the drug development of neurodegenerative diseases.